Influence of sociodemographic characteristics on perception of tourism development impact - Stojković, Ilinka; Tepavčević, Jelena; Blešić, Ivana; Ivkov, Milan; Šimon, Viktorija (The European Journal of Applied Economics, 2020)
Residents play an important role in the process of destination development, but a supportive attitude in regard to tourism is key to the success of the destination. Various authors have examined residents’ attitudes towards the impacts of tourism development from different points of view. This paper aimed to investigate the impacts of sociodemographic characteristics of locals on their attitudes towards tourism development. The study was conducted on the territory of Sirnićka Župa, in the municipality of Štrpce. A total of 94 respondents were included in the research. The results indicated that gender and education level have not influenced residents’ attitudes. On the other hand, it has been found that the age and length of residents’ significantly influence residents’ attitudes towards tourism development impacts.
Keywords: Sirnićka Župa, residents, tourism development, tourism impacts, sociodemographic characteristics